Application for the Differentiated Learning Model in Office Management and Business Services - Muhammad Alief Gunawan; Sirajuddin Saleh; Muh Darwis; Elfira Elfira (International Journal of Administration and Education (IJAE), 2025)
This study focuses on the application of a differentiated learning model in the basic subjects of office management and business services class X MPLB at SMK Wahyu 1 Makassar. This study aims to determine how a differentiated learning model is applied in the basics of office management and business services for class X at SMK Wahyu 1 Makassar. This study utilizes a descriptive qualitative approach by involving research informants in data collection, namely, the head of the MPLB department, teachers of basic subjects of Office Management and Business Services, MPLB teachers, and class X students of the MPLB department. Data collection is carried out by observation, interview, and documentation techniques; then the data is analyzed through the process of data condensation, data presentation, and conclusion drawing. The results of this study show that the application of a differentiated learning model in the basic subjects of office management and business services class X MPLB at SMK Wahyu 1 Makassar, when viewed from the three indicators, can be said to be effective. The research results for each indicator provide evidence of its effectiveness: The Preparation Stage is not effective because there is a gap between real implementation in the field which results in students' learning experiences not really reflecting real differentiated learning. The Implementation Stage has been effective because teachers have successfully demonstrated creativity in identifying students' interests through concept maps to explore initial knowledge, relate theory to students' real experiences, theoretical aspects to practice, even though limited by predetermined learning outcomes. The Evaluation Stage is effective because it shows using various forms of assessment such as pre-test and post-test to monitor students' level of understanding, as well as providing direct feedback as a form of appreciation and correction to their work results.